Pengaruh Penggunaan Model Pembelajaran Problem Based Learning dengan Menggunakan Aplikasi WA Forum dalam Upaya Meningkatkan Motivasi Belajar Pada Siswa SMAN 1 Ranah Pesisir Selama Pandemi Covid 19 - Kesi Fitriani; Armida S (Universitas Negeri Padang, 2023)
This study aims to determine how the influence of the Problem Based Learning (PBL) learning model with the use of the whatsapp forum application on student motivation at SMAN 1 Ranah Pesisir school during the covid-19 pandemic. This type of research is a quantitative descriptive study using SPSS version 16.0. The data used are primary data and secondary data. The data collection technique is by using a questionnaire and documentation. The population in this study is the teaching staff/teachers of SMAN 1 Ranah Pesisir who apply the model and media according to what the researchers did. The sampling technique used was random sampling with a total of 35 respondents. The instrument trial used validity and reliability tests. Data analysis with descriptive analysis of normality test, homogeneity of variance test, hypothesis testing using F test and t test. The results of this study are Problem Based Learning (PBL) learning models using the whatsApp forum application can increase student learning motivation at SMAN 1 Ranah Pesisir schools. Based on the results of the study, to increase students' learning motivation, it is expected that teachers can make whatsapp forums as one of the learning media in Problem Based Learning (PBL) learning. For students, they must be able to increase their learning motivation by utilizing the WhatsApp forum media with the Problem Based Learning (PBL) learning model and for schools, they must be able to facilitate teachers during the online learning process at SMAN 1 Ranah Pesisir schools.